Flávio de Carvalho : uma filogenética vestimentar - Arruda, Luisa Mendes (2016)
This study aims at analysing clothing that is present in the artistic and literary work by Flavio de Carvalho. It highlights dress as a determining factor in the process of personal identification within the scenic dimension of the city. At the same time,